Head, face, and neck cooling for performance: a systematic review and meta-analysis - Stevens, C. J.; Borg, D.; Brade, C.; Carter, S.; Filingeri, D.; Lee, J.; Lim, L.; Mündel, T.; Taylor, L.; Tyler, C. J. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Cooling the head, face, and neck can have strong perceptual effects that contribute to improved performance. This systematic review aimed to determine the effect of cooling strategies targeting the head, face, and neck on physical and cognitive performance, determine any associated physiological and perceptual responses, synthesize adverse events, and provide practical applications.